Bank Efficiency and Profitability in Singapore: A Stochastic Frontier Approach - Wang, Lei (2013)
This study examines the bank efficiency and the determinants of bank profitability of nine commercial banks in Singapore over the period 2005-2012. A two-stage Stochastic Frontier Approach is used to estimate the cost efficiency and the profit efficiency, and a fixed effect panel data analysis is applied to test the determinants of bank profitability. The findings indicate that the profit efficiency of Singaporean banks is more heavily impacted by the Global financial crisis than the cost efficiency. Large banks are more profit efficient and less cost efficient than small banks. The exogenous factors, bank size and the market share, are significantly positively related to the profit efficiency and negatively related to the cost efficiency. Overall, there is still room for Singaporean banks to improve their cost efficiency and profit efficiency. On the other hand, bank profitability of Singaporean banks is negatively affected by the equity to total assets ratio, cost to income ratio and bank size. In contrast, the improvement in the profit efficiency can be greatly in favour of bank profitability.